How can insulin initiation delivery in a dual-sector health system be optimised? A qualitative study on healthcare professionals' views - Lee, P.Y.; Lee, Y.K.; Ng, C.J. (BioMed Central, 2012)
Background: The prevalence of type 2 diabetes is increasing at an alarming rate in developing countries. However, glycaemia control remains suboptimal and insulin use is low. One important barrier is the lack of an efficient and effective insulin initiation delivery approach. This study aimed to document the strategies used and proposed by healthcare professionals to improve insulin initiation in the Malaysian dual-sector (public-private) health system. Methods: In depth interviews and focus group discussions were conducted in Klang Valley and Seremban, Malaysia in 2010-11. Healthcare professionals consisting of general practitioners (n = 11), medical officers (n = 8), diabetes educators (n = 3), government policy makers (n = 4), family medicine specialists (n = 10) and endocrinologists (n = 2) were interviewed. We used a topic guide to facilitate the interviews, which were audio recorded, transcribed verbatim and analysed using a thematic approach. Results: Three main themes emerged from the interviews. Firstly, there was a lack of collaboration between the private and public sectors in diabetes care. The general practitioners in the private sector proposed an integrated system for them to refer patients to the public health services for insulin initiation programmes. There could be shared care between the two sectors and this would reduce the disproportionately heavy workload at the public sector. Secondly, besides the support from the government health authority, the healthcare professionals wanted greater involvement of non-government organisations, media and pharmaceutical industry in facilitating insulin initiation in both the public and private sectors. The support included: training of healthcare professionals; developing and disseminating patient education materials; service provision by diabetes education teams; organising programmes for patients' peer group sessions; increasing awareness and demystifying insulin via public campaigns; and subsidising glucose monitoring equipment. Finally, the healthcare professionals proposed the establishment of multidisciplinary teams as a strategy to increase the rate of insulin initiation. Having team members from different ethnic backgrounds would help to overcome language and cultural differences when communicating with patients. Conclusion: The challenges faced by a dual-sector health system in delivering insulin initiation may be addressed by greater collaborations between the private and public sectors and governmental and non-government organisations, and among different healthcare professionals.